Engineering trustworthy software systems : third International School, SETSS 2017, Chongqing, China, April 17-22, 2017, Tutorial lectures /: third International School, SETSS 2017, Chongqing, China, April 17-22, 2017, Tutorial lectures. (2018) - Unknown
No abstract available